Dynamics of Organizational Behavior of Kebarongan Village Government Apparatus in the Provision of Public Services - Siti Zulaihah; Denok Kurniasih (Edujavare Publishing, 2025)
This study examines the organizational behavior of Kebarongan Village Government officials in providing public services. The village government is the bureaucratic unit closest to the community, so the behavior of its officials greatly determines the quality of service. This study uses a descriptive qualitative approach with data collection techniques through interviews, observations, and document reviews. Analysis is carried out in stages through data reduction, data presentation, and drawing conclusions. The theoretical framework used is Max Weber's bureaucratic theory which emphasizes the characteristics of rational organizations, namely the existence of formal rules, hierarchy of authority, division of labor, impersonality, professionalism, and an orientation towards efficiency. The results show that the behavior of Kebarongan Village Government officials still reflects the character of classical bureaucracy, especially in the application of formal rules and hierarchical structures. However, the aspect of impersonality has not fully implemented because there are still service practices influenced by social proximity and kinship. Professionalism of officials is also beginning to be seen through training and capacity building, but is still limited by human resources. This study concludes that the organizational behavior of village officials is at the intersection of the Weberian bureaucratic model and local socio-cultural conditions. This shows that bureaucracy at the village level does not fully operate according to the rational-legal model, but experiences adjustments to the realities of society. These findings are expected to enrich public administration studies, particularly regarding the dynamics of public sector organizations at the village level.